HUBUNGAN KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR MAHASISWI SEMESTER II AKADEMI KEBIDANAN SEHAT MEDAN TAHUN 2017 - Herlia sumardha (Jurnal Maternitas Kebidanan, 2019)
Emotional Intelligence is one of the factors that influence a person's success, because IQ contributes 20% to one's success, while 80% contributes from other factors, one of which is emotional intelligence. The purpose of this study was to determine the relationship of emotional intelligence with second semester student achievement Akademi Kebidanan Sehat Medan tahun 2017. This study uses a quantitative type of study through a cross sectional approach. The sample in this study was mahasisiwi second semester of the Academy of Health Midwifery with 43 respondents with total sampling technique. Data analysis techniques are done using Chi Square. The results showed that emotional intelligence was in the moderate category, and learning achievement in the category was very satisfying. There is a Relationship between Emotional Intelligence and Student Achievement in Semester II in Akademi Kebidanan Sehat Medan Tahun 2017 with p value 0,004. The conclusion of the study shows that there is an emotional intelligence relationship with the learning achievement of the second semester students of the Medan Healthy Midwifery Academy and for the place it is hoped that they can provide input material to provide students with regular emotional intelligence tests.